Check, counter & control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Animal Trypanosomosis: Diagnosis and Epidemiology Published by the FAO and the IAEA, 2000. 256 pp. ISBN 90 5782 065 x Free of charge